Physical activity, fatigue and sleep quality at least 6 months after mild traumatic brain injury in adolescents and young adults: A comparison with orthopedic injury controls. (September 2019) - van Markus-Doornbosch, Frederike; Peeters, Els; Volker, Gerard; van der Pas, Stéphanie; Vliet Vlieland, Thea; Meesters, Jorit
Abstract: Objectives: To compare physical activity (PA), fatigue and sleep quality in adolescents and young adults (AYAs) after mild TBI (mTBI) to persons of similar age after orthopedic injury (OI) on the longer term. Setting: Follow-up at least 6 months after visiting the emergency department of one of 2 general hospitals. Participants: Forty-nine patients aged 12–25 years (mean 18.4 years), diagnosed with mTBI and 54 patients aged 12–25 years (mean 15.8 years) with OI. Design: Cross-sectional electronic survey study. Main outcome measures: The Activity Questionnaire for Adults and Adolescents with results dichotomized for meeting/not meeting Dutch Health Enhancing PA recommendations (D-HEPA), the Checklist Individual Strength (range 20–140, low-high) measuring fatigue, and the Pittsburgh Sleep Quality Index (range 0–21, high-low) measuring sleep quality were administered. Results: Patients with mTBI less frequently met D-HEPA recommendations than patients with OI (49% vs. 70%; OR 2.87, 95%CI 1.07, 7.72) and reported more concentration-related fatigue problems (mean 19.1 (SD 8.0), mean 13.9 (SD 7.8), respectively; β 3.98, 95%CI 0.39, 7.56), after adjusting for potential confounders, sex, BMI, age and time since injury. No differences were found in sleep quality. Conclusions: Identifying symptoms and limitations in activities is important after mTBI so that rehabiliation treatment can be initiated. Whether physical activity or fatigue is the best target for treatment remains to be established. Highlights: 51% of youth with mild TBI do not meet physical activity recommendations. Youth with mild TBI report more fatigue than those with an orthopedic injury. Youth with mild TBI or orthopedic injury report similar sleep quality.